2020
DOI: 10.3892/ol.2020.12253
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulated microRNA‑140‑5p expression regulates apoptosis, migration and invasion of lung cancer cells by targeting zinc finger protein 800

Abstract: Despite advances in the diagnosis and treatment in recent years, lung cancer is still one of the primary causes of cancer-associated morbidity and mortality in globally. Abnormally expressed microRNAs (miRNAs/miRs) in tumor tissues serve vital roles in the pathological mechanism of tumors and have become prospective biomarkers for cancer diagnosis. The present study aimed to investigate the effects of the miR-140-5p/zinc finger protein 800 (ZNF800) axis in lung carcinoma, and determine its potential underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Cleaved caspase-3 is an apoptosis-related protein (24). Since mR-616-3p was found to promote apoptosis in HUVECs, western blotting analysis was used to determine whether miR-616-3p affects the expression of cleaved caspase-3 protein.…”
Section: Inhibition Of Mir-616-3p Expression Inhibits the Expression Of Cleaved Caspase-3 Protein In Huvecsmentioning
confidence: 99%
“…Cleaved caspase-3 is an apoptosis-related protein (24). Since mR-616-3p was found to promote apoptosis in HUVECs, western blotting analysis was used to determine whether miR-616-3p affects the expression of cleaved caspase-3 protein.…”
Section: Inhibition Of Mir-616-3p Expression Inhibits the Expression Of Cleaved Caspase-3 Protein In Huvecsmentioning
confidence: 99%
“…These findings may contribute to further understanding the mechanism of liver I/R injury and may provide novel insights into liver I/R. miR-140-5p has been extensively studied in tumor and non-tumor diseases and has exhibited favorable results (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)38). There is still a large gap in applying miR-140-5p research results to benefit patients clinically.…”
Section: Discussionmentioning
confidence: 95%
“…Other miRNAs, such as miR-125b, miR-128-3b and miR-450b-5p ( 5 , 6 , 8 ), are reportedly involved in liver I/R. miR-140-5p has been investigated extensively in tumor research, including glioma, breast and lung cancer, and hepatocellular carcinoma ( 13 , 14 , 17 , 18 ). miR-140-5p has also been extensively studied in non-tumor diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, its role in regulating breast tumor angiogenesis and metastasis in response to hypoxia needs to be evaluated. Several cancers, including breast [ 13 , 14 , 15 ], gastric [ 16 , 17 ], lung [ 18 ], multiple myeloma [ 19 ], retinoblastoma [ 20 ], laryngeal squamous cell carcinoma (LSCC) [ 21 ], and nephroblastoma [ 22 ], have shown reduced expression of miR-140-5p which played a crucial role in cancer progression. In the current study, we observed significant repression of miR-140-5p in BC cells under hypoxia.…”
Section: Introductionmentioning
confidence: 99%